Ortalamayı Öldürmek, Azınlığı Güçlendirmek: Üretken Yapay Zeka, Sosyal Medya Örüntüleri ve Akademik Çalışmanın Yapısal Krizi (Üçüncü Sektör Sosyal Ekonomi Dergisi, 2026)
This article rejects the dominant framing of generative AI in academia as merely a problem of plagiarism, laziness and cheating, and instead reads it as a symptom and accelerator of a structural crisis in the regime of academic labour. It asks two related questions: through which mechanisms does generative AI transform an already metricised and standardised academic production system, and why can this transformation not be adequately captured within the narrow frame of “ethics violations”? Drawing on conceptual analysis and a targeted reading of recent empirical and methodological studies, the article argues that generative AI automates the bulk of “average academic work” – literature summarising, template filling, low-risk repetition – while acting as a powerful multiplier for a small minority of researchers who possess genuine theoretical depth and original insight. At the same time, the spread of synthetic data and synthetic participants raises new questions about what still counts as empirical research when “data” can be generated without encounter with the world. Situating these developments within audit culture, algorithmic infrastructures and the attention economy of social media, the article contends that the real risk of generative AI is not simply individual misconduct but a further algorithmic colonisation of academic subjectivity itself. It concludes by sketching institutional implications for evaluation criteria, the cautious use of synthetic data and the protection of slow, risky and original work.
Keywords: Bilgi üretim rejimi; akademik kapitalizm; üretken yapay zeka; özgün düşünce; akademik emeğin otomasyonu